Whole slide imaging: The futurescape of histopathology - Jayaram N Iyengar (Wolters Kluwer Medknow Publications, 2021)
The last two decades have seen considerable progress in the use of digital technology in histopathology. Digital photography of microscopic slides and the use of static images gave way to robotic microscopes. These technologies had their own limitations that precluded their widespread use. Creation of whole slide scanners that can produce digitized whole slide images (WSI) and the "comparable to conventional microscope" experience opened multiple avenues for their utilization not only in specific applications such as expert consults, quality assessment programs, education and archiving, but also for routine day-to-day reporting. Industry pressures driven by consumer requirements have led to great development in image quality, speed of scanning, size of stored files, and capital cost of scanners. User-friendly software and analytical algorithms have further enhanced user experience. Challenges that need to be either accepted or overcome would include capital expense not significantly yielding a return on investment, and management of storage space. This review attempts to take the reader through the evolution of WSI scanners and to share the author's experience with WSI for routine histopathology reporting, education, and external quality assessment along with a review of available literature.